College of education faculty mobility in relation to certain variables - Fonollera, Maura B. 1939- (s.n.], 1969)
Using the descriptive survey method, the author determined the mobility of the college of education faculty members of private universities in the city of Manila with the objective of exposing certain needs and problems of teachers that must be met and solved to enable them to fulfill their roles in guiding the youth of the land.